Dunhill Malaysia Cup : does sports sponsorship have a direct effect on corporate image - Amiruddin, Zain Azmy (2000)
Malaysian football with its glorious history has always been the centre of all sports in Malaysia. Being the No. 1 sport in Malaysia, it comes under close scrutiny from sports critics and the watch full eyes of the media, more so when football receives good support from all quarters including fans, sponsors and the media. Sponsorship of sports has become an integral part of the marketing mix of the corporate world with corporations devoting large amounts of money to associate themselves with sport and it particular identity. However, sponsors have become increasingly prudent with their sponsorship dollar with a 'tingly feeling' of association not enough to justify the aounts of money required to become a sponsor of a top-level sport. The main objective of this research is to gather an in-depth knowledge of the relationship between sponsorship and corporate image. Besides looking into criteria selection process of the sponsorship programme, we are looking into other factors, which could explain why corporate sector sponsor sports events.